(untitled) - Heifetz, Ronald A. (Boston, Mass., 2009)
The book is anchored in the framework of Adaptive Leadership, but goes beyond the theory to provide a practical set of stories, diagrams, techniques, and activities that will help you both assess and address the toughest challenges that lie ahead. Dozens of tools and tactics are presented in an exciting, clear, and reader-friendly design.
Keywords: Leadership,Organizational change